1995
DOI: 10.1121/1.413317
|View full text |Cite
|
Sign up to set email alerts
|

Electrode ranking of ‘‘place pitch’’ and speech recognition in electrical hearing

Abstract: The ability to distinguish electrical stimulation of different electrodes on the basis of "pitch or sharpness" was evaluated with an electrode ranking procedure in 14 individual users of the Nucleus cochlear implant. Prior to the electrode ranking test, absolute thresholds and maximum comfortable loudness levels were measured, and loudness balancing was accomplished across all usable electrodes. Performance on the electrode ranking task was defined in terms of d' per mm of distance between comparison electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
107
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 19 publications
16
107
2
1
Order By: Relevance
“…Several publications have confirmed that the pitch perceived generally increases when a constant-rate pulse train is presented on one electrode at a time, and the position of the active electrode is moved from an apical to a more basal location in the cochlea (Tong and Clark, 1985;Townshend et al, 1987;McDermott and McKay, 1994;Nelson et al, 1995;Zwolan et al, 1997).…”
Section: Pitch Associated With Place Of Stimulationmentioning
confidence: 93%
“…Several publications have confirmed that the pitch perceived generally increases when a constant-rate pulse train is presented on one electrode at a time, and the position of the active electrode is moved from an apical to a more basal location in the cochlea (Tong and Clark, 1985;Townshend et al, 1987;McDermott and McKay, 1994;Nelson et al, 1995;Zwolan et al, 1997).…”
Section: Pitch Associated With Place Of Stimulationmentioning
confidence: 93%
“…Psychophysical studies which have investigated the ability to discriminate between stimulation on different electrodes also indicate that the perception of spectral cues is a performance-limiting factor in CI speech perception ͑Collins et al Donaldson and Nelson, 2000;Henry et al, 2000;Nelson et al, 1995;Throckmorton andCollins, 1999͒. Henry et al ͑2000͒ showed a correlation between speech perception and electrode discrimination in the frequency regions below approximately 2.7 kHz when the stimuli in the electrode discrimination task were presented with randomly varying levels, but no correlation between the two measures in the frequency regions above 2.7 kHz, indicating that fine spectral discrimination may be relatively more important in the vowel-formant regions than in the high-frequency regions, where the cues are mostly broadband.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the tonotopicity seen in the CI is not perfect in all subjects. Some subjects cannot discriminate between the pitches across different electrodes and/or a more basal electrode may sound lower in pitch than a more apical one (so called pitch reversal) (Busby et al, 1994;Cohen et al, 1996;Nelson et al, 1995;Donaldson and Nelson, 2000). Spatial separation between electrodes has also been found to affect CI users' pitch perception ability.…”
Section: Spectral/ Place Pitch Codingmentioning
confidence: 99%
“…Spatial separation between electrodes has also been found to affect CI users' pitch perception ability. Increased separation improved pitch ranking performance of CI subjects (Nelson et al, 1995;Tong and Clark, 1985). In addition, most CI listeners cannot make full use of the spectral information available through their implants.…”
Section: Spectral/ Place Pitch Codingmentioning
confidence: 99%